The impact and lessons learnt from the COVID-19 pandemic on a UK Burns Centre. Issue 7 (November 2021) - Phillips, Georgina S.A.; Talwar, Cyrus; Makaranka, Stanislau; Collins, Declan P.
Highlights: Public concern of catching COVID-19 has led to preventable burn injuries and delays in seeking medical attention. Infection rates are higher in patients with delayed presentation to burns services (26% compared to 6%). A more conservative and flexible approach to burn management has enabled to safe delivery of care during the pandemic. The burns Outreach team is invaluable in safely treating vulnerable shielding patients. Patient education and the use of telemedicine reduces clinic appointments required. Abstract: The COVID-19 pandemic has dramatically impacted healthcare provision in the UK and burns services have had to adapt to ensure the continuity of a safe care. As we return to "normality" we reflect on lessons learnt from our response to this pandemic. A service evaluation was performed from patient notes between March 23rd and May 8th 2020 and an anonymous survey given to patients attending outpatient appointments. 258 patients were referred to our burns service and 148 patients completed the survey. Eleven burns were caused by treatment or prevention of COVID-19. Patients delayed seeking medical attention due to concern of catching COVID-19 (36% adults, 8% children). There was a delay in referral of 17 patients despite them fulfilling the referral criteria. Infection rates were higher following delayed presentation (21% vs 6%). The majority of burns were managed conservatively (237/258). Dressing changes were performed at home by 32% of patients. The outreach team treated 22 patients. During the pandemic telemedicine has improved the efficiency of outpatient burn care and outreach nurses have enabled treatment of vulnerable patients. More must be done to raise public awareness of preventable causes of burn injury and to reassure them to seek help when burns occur.